New tool to support monitoring and reporting rice production all all levels - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
The tool was developed based on the current reporting needs and requirements of central and local Crop Production Departments. It is being piloted in Can Tho city, Vietnam,